SOCIOLOGICAL STUDY OF OPINIONS AND JUDGMENTS ABOUT THE PLACE AND ROLE OF SANATORIUMS IN HUMAN LIFE - Madakhanov , Akbarjan; Shamatov, Islom; Xalilov , Izzatillo (Medical science of Uzbekistan, 2023)
The activity of the use of health care services in the article notes that demographic, socio-economic factors, and an integrated indicator caused by the conditions in associated with the body functionality of the body. Based on the results of the acquisition of sociological research, the role of the sanatories in human life analyzed the content and essence of the role and remarks of the sanences in human life and its role in human life. The same is shown that the opinion of the population about healthcare is not fully formed and the shallowness of the feedback. In filling this procedure, scientists and specialists of industry, doctoral and prevention institutions and health facilities and sanatoriums will focus on the need for doctors, as well as the work of tour operators. It is also noted that the activities of health care activities, including further improvement of the activities of events to decide the role and role of human life in human life.